Enhancing Speaking Ability Through Pop-Up Card: Its Effects on Students’ Speaking Proficiency - Kristianingsih, Kristianingsih (Journal of Linguistics and Social Sciences, 2023)
The primary aim of this study is to assess the efficacy of employing pop-up card media to enhance students' speaking proficiency during the initial semester of eighth grade at SMPN 2 Gadingrejo in the 2020/2021 academic year. In this study, the researcher employed a quasi-experimental design consisting of two distinct classes: experimental and control classes. The experimental group received instruction utilizing pop-up cards, whereas the control group received instruction utilizing textbooks. Each class was administered the identical pre-test and post-test. The investigator employed an oral examination as a means of data collection for the research. The research sample consisted of eighth-grade students from SMPN 2 Gadingrejo. The research samples comprised two classes, VIII 1 and VIII 2, with 62 students. The experimental class consisted of 30 students, while the control class had 32 students. The researcher analyzed the data using an independent sample t-test. The analysis results indicated that the utilization of pop-up card media positively impacted the speaking ability of students at SMP N 2 Gadingrejo during the academic year 2020/2021. The data analysis conducted using SPSS yielded a significance value (Sig) of 0.000 and an alpha level (α) of 0.05. The acceptance of Ha is indicated by the p-value of 0.000 is less than the significance level of 0.05. Hence, the utilization of pop-up card media demonstrated efficacy in enhancing the speaking proficiency of eighth-grade students at SMPN 2 Gadingrejo during the first semester of the 2020/2021 academic year. The findings also indicated that pop-up card media could be a viable alternative for instructing speaking skills.